Multiple choice questions in intensive care medicine - Benington, Steve; Nightingale, Peter; Shelly, Maire P. (Tfm Pub., 2009)
Features practice MCQs divided into three practice papers. This book is accompanied by short referenced notes drawing from journal articles, critical care textbooks and selected internet resources. It is suitable for junior intensive care trainees, intensive care consultants as a teaching aid, and trainees preparing for professional examinations.